STRATEGI ORGANISASI AIESEC MELALUI PROGRAM AFL (AIESEC FUTURE LEADERS) DALAM SOLIDARITAS GLOBAL SEBAGAI DAYA DUKUNG SDG TUJUAN 4.7 DI INDONESIA - Fadhlan A. (2023)
The global problems that are reflected and targeted in the SDGs (Sustainable Development Goals) do not always have to be carried out by one of the main actors who play in managing these policies. AIESEC as an nongovernmental organisation that contains people who have solidarity for cooperation aimed at mutual benefit without thinking about the boundaries of the state's interests in a national sovereignty. That way this research tries to see the efforts and steps taken by AIESEC Indonesia, one of them is the AFL program to support the fulfillment of target number 4 (especially 4.7) which must be achieved immediately to eliminate real problems faced in various parts of the world. Not only that, this research wants to see how an organization that has existed since 1948 always updates its plans and goals in strengthening peace efforts as a global NGO. The research method used a qualitative description which is useful in explaining a real-situation research topic and describing a descriptive and complete study. The results of this research obtained that AIESEC through AFL has implemented programs that can provide support for global citizenship knowledge and sustainable perspective. Even if we look at it quantitatively, the achievement is seen by the Indonesian government as a measurement of success from the goal 4.7 by means of calculating data from the formal education aspects (primary and secondary education).